2017
DOI: 10.2217/imt-2017-0062
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD 19 and Anti-CD 20 CAR-Modified T Cells for B-Cell Malignancies: A Systematic Review and Meta-Analysis

Abstract: Chimeric antigen receptor modified T cells targeting CD19 and CD20 have shown activity in Phase I, II trials of patients with hematological malignancies. We conducted a systematic review and meta-analysis of all published clinical trials studying the role of efficacy as well as safety of CD-19 and CD-20 chimeric antigen receptor-T therapy for B-cell hematologic malignancies. A total of 16 studies with 195 patients were identified. The pooled analysis showed an overall response rate of 61% (118/195) with comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 51 publications
2
20
0
Order By: Relevance
“…The overall pooled RR (CR+PR) of CD19-CAR-T cells was 72% (95% CI: 62À77%), which is in agreement with previously published meta-analyses. In one analysis, the pooled CR rate was 55% and PR was 25% [13], whereas another analysis showed an overall response rate of 61% with CR of 42% and PR of 19% [12], and an overall pooled RR of 48% was reported in one study [10]. Thus, most analysis demonstrated that CAR-T therapy is effective in B-cell malignancies, and our analysis also elucidated associations between clinical response and clinical parameters that have not been previously examined in other meta-analysis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The overall pooled RR (CR+PR) of CD19-CAR-T cells was 72% (95% CI: 62À77%), which is in agreement with previously published meta-analyses. In one analysis, the pooled CR rate was 55% and PR was 25% [13], whereas another analysis showed an overall response rate of 61% with CR of 42% and PR of 19% [12], and an overall pooled RR of 48% was reported in one study [10]. Thus, most analysis demonstrated that CAR-T therapy is effective in B-cell malignancies, and our analysis also elucidated associations between clinical response and clinical parameters that have not been previously examined in other meta-analysis.…”
Section: Discussionmentioning
confidence: 98%
“…In this analysis, the overall pooled RR of CD19-CAR-T cells was 73% and 93% in ALL patients and 36% in lymphoma patients. In 2017, a systematic review and meta-analysis including anti-CD19 and anti-CD20 CAR-modified T cells were involved in 16 studies with 195 patients [12]. The pooled analysis showed an overall RR of 61%.…”
Section: Introductionmentioning
confidence: 99%
“…Use of the non-myeloablative transplant regimen containing fludarabine and cyclophosphamide improved overall response rates compared to patients who did not receive preconditioning, and this regimen therefore was taken forward in a majority of subsequent engineered ACT studies [13]. ACT engineered with chimeric antigen receptors (CARs) and high affinity T-cell receptors (TCRs) targeted against tumor-specific antigens have shown promise in the clinic [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…An example regulatory pathway includes PD-1/programmed cell death protein ligand 1 (PD-L1), which acts as a negative feedback loop to switch off adaptive immunity following the initial immune response (11). The CAR-T and PD-1 blockade techniques have achieved notable results in the therapy numerous types of cancers (12,13). However, a number of clinical trials have demonstrated that the efficacy of CAR-T and PD-1 blockade therapy remains limited (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%